Diffusion resisting performance of concrete modified with sodium methyl silicate in saline soil area. (3rd October 2022) - Chen, Longlong; Wang, Yaqiong; Wang, Zhi-Feng; Chang, Hongtao; Fan, Feifei
Highlights: A new type of concrete mixed 2.4% sodium methyl silicate was prepared. An instantaneous diffusion model of chloride ions in concrete was proposed. The diffusion reducing performance of the new concrete were compared against ordinary concrete. A useful means for the corrosion resistance of tunnel lining was proposed. Abstract: Concrete of tunnel lining in saline soil area is subjected to compound salt attacks, which decrease the service life of tunnel. In this study, a new type of concrete mixed 2.4 % sodium methyl silicate was prepared to improve the compound salt damage resistance of concrete. The properties of the concrete, including chloride diffusion resisting performance, compressive strength, and water absorption, were investigated. The results showed that the chloride diffusion resisting performance of the concrete modified with methyl sodium silicate was notably better than that of normal concrete in compound salt solution. The maximum compressive strength had not changed significantly compared with normal concrete, while the occurrence of peak strength was delayed by about 30 days. The water absorption of the concrete modified with sodium methyl silicate was reduced by 21.09 % compared with the normal concrete. Moreover, chloride diffusion resisting mechanism of the concrete immersed in compound salt solution was elucidated. Furthermore, based on the Fick's second law and experimental results, a time-varying diffusion model for predicting the chloride ion mass fraction of chloride in the concrete was proposed in this paper. The proposed approach is a useful means for the chloride diffusion resisting of concrete in some saline soil area of Western China.